2010
DOI: 10.1007/s10584-010-9971-x
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas taxes on animal food products: rationale, tax scheme and climate mitigation effects

Abstract: Agriculture is responsible for 25-30% of global anthropogenic greenhouse gas (GHG) emissions but has thus far been largely exempted from climate policies. Because of high monitoring costs and comparatively low technical potential for emission reductions in the agricultural sector, output taxes on emission-intensive agricultural goods may be an efficient policy instrument to deal with agricultural GHG emissions. In this study we assess the emission mitigation potential of GHG weighted consumption taxes on anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
169
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(175 citation statements)
references
References 37 publications
2
169
2
2
Order By: Relevance
“…A Danish study (Edjabou and Smed 2013) found that a carbon tax on food could decrease the carbon footprint from food for an average household by up to 10%-20%. Wirsenius et al (2011) found that GHG weighted consumption taxes on animal food products in the EU could reduce emissions from EU agriculture by 7%. Nordgren (2012aNordgren ( , 2012b) makes a moral argument in favour of a climate tax on in the first instance the consumption of ruminant meat.…”
Section: Recommendations For a Tax On Ruminant Meat As A First Stepmentioning
confidence: 99%
“…A Danish study (Edjabou and Smed 2013) found that a carbon tax on food could decrease the carbon footprint from food for an average household by up to 10%-20%. Wirsenius et al (2011) found that GHG weighted consumption taxes on animal food products in the EU could reduce emissions from EU agriculture by 7%. Nordgren (2012aNordgren ( , 2012b) makes a moral argument in favour of a climate tax on in the first instance the consumption of ruminant meat.…”
Section: Recommendations For a Tax On Ruminant Meat As A First Stepmentioning
confidence: 99%
“…educational campaigns) and legal instruments. Many arguments have been made in favour of a meat consumption tax, rather than a meat production tax (79)(80)(81) . It has even been suggested by Chatham House that without government intervention consumers are unlikely to reduce their consumption of animal-based produce (62) .…”
Section: Public Health Nutritionmentioning
confidence: 99%
“…An altered diet is both an effective and possibly necessary mitigation strategy to reach long-term climate targets; it is also interesting from a health perspective (Friel et al, 2009;Westhoek et al, 2011). Since the cost of monitoring emissions would be very high in agriculture and large emissions reduction can be achieved by changing consumption patterns, Wirsenius et al (2011) proposed a GHG-weighted consumption tax on meat, dairy and eggs. Such a tax would be neutral between domestic and imported animal products, and would provide incentives for the consumer to change their eating patterns towards less emission-intensive food types.…”
Section: Drivers Of Changes In Emissions Intensities In Productionmentioning
confidence: 99%